Cognitive-behavioral and psychodynamic therapy in adolescents with social anxiety disorder: a multicenter randomized controlled trial - Salzer, Simone; Stefini, Annette; Kronmüller, Klaus-Thomas; Vonderlin, Eva (Psychotherapy and psychosomatics, 2018)
Background: Although social anxiety disorder (SAD) has an early onset and is frequently found in adolescence, evidence for psychotherapeutic treatments of SAD in adolescents is rather scarce. Within the Social Phobia Psychotherapy Research Network (SOPHO-NET), we examined the efficacy of cognitive-behavioral (CBT) and psychodynamic therapy (PDT) compared to a waiting list (WL) in these patients. Methods: In a multicenter randomized controlled superiority trial, 107 patients, aged 14-20 years, were randomized to CBT (n = 34), PDT (n = 34), or WL (n = 39). Assessments were made at baseline, at the end of treatment, and 6 and 12 months after termination. The Liebowitz Social Anxiety Scale for Children and Adolescents (LSAS-CA) applied by raters masked to the treatment condition was used as the primary outcome. As secondary outcomes, rates of response and remission and the Social Phobia Anxiety Inventory (SPAI) were used. Results: Both treatments were superior to WL in the LSAS-CA (CBT: p = 0.0112, d = 0.61, 95% CI 0.14-1.08; PDT: p = 0.0261, d = 0.53, 95% CI 0.06-1.00). At the end of treatment, response rates were 66, 54, and 20% for CBT, PDT, and WL. The corresponding remission rates were 47, 34, and 6%, respectively. CBT and PDT were significantly superior to WL regarding remission (CBT: p = 0.0009, h = 1.0; PDT: p = 0.0135, h = 0.74), response (CBT: p = 0.0004, h = 0.97; PDT: p = 0.0056, h = 0.72), and the SPAI (CBT: p = 0.0021, d = 0.75, 95% CI 0.27-1.22; PDT: p = 0.0060, d = 0.66, 95% CI 0.19-1.13). Treatment effects were stable at 6- and 12-month follow-ups. Conclusions: These results are comparable to the large SOPHO-NET trial in adults (n = 495). Early treatments for social anxiety are needed in order to prevent chronic manifestation of SAD.
Gesehen am 16.05.2019